2013
DOI: 10.5539/jas.v5n8p231
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resveratrol on the Quality of Extended Boar Semen During Storage at 17ºC

Abstract: The natural polyphenol resveratrol may be beneficial to many aspects of cell function and animal health, although its actions in the male reproductive system vary depending on animal species. This work investigates resveratrol effects on the quality of preserved boar semen during liquid storage at 17ºC. We used three approaches: 1) evaluation of conventional parameters of seminal quality, 2) measurement of specific response to capacitating stimuli, and 3) evaluation of mitochondria membrane potential and ATP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
(51 reference statements)
3
13
0
Order By: Relevance
“…The inhibitory effect of resveratrol (Martín-Hidalgo et al, 2013) and quercetin (Johinke et al, 2014) on the sperm Kinematic of different species has been reported, particularly when used at high concentrations. In this study, with the exception of the oscillation index (WOB) at time 0h, treating goat semen with different concentrations (0,15,25,50,75 and 100µM) of trans-resveratrol or quercetin did not alter the sperm kinematics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of resveratrol (Martín-Hidalgo et al, 2013) and quercetin (Johinke et al, 2014) on the sperm Kinematic of different species has been reported, particularly when used at high concentrations. In this study, with the exception of the oscillation index (WOB) at time 0h, treating goat semen with different concentrations (0,15,25,50,75 and 100µM) of trans-resveratrol or quercetin did not alter the sperm kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between studies released with the use of resveratrol and quercetin polyphenols have been attributed to the dose and differences between species (Moretti et al, 2012;Martín-Hidalgo et al, 2013). According to the species, enzymes that are directly or indirectly linked to sperm motility maintenance, such as Ca 2+ -ATPase (Nass-Arden and Breitbart, 1990), F0F1-ATPase (Zheng and Ramirez, 2000) and cyclooxygenase (COX) (Kowalska et al, 2011), are inhibited to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…In the boar, various doses of RSV (10, 33, 66, and 100 mM) supplemented during semen preservation at 17 C for 7 days did not improve sperm quality parameters [22].…”
Section: Introductionmentioning
confidence: 99%
“…We already demonstrated that resveratrol is ineffective for improving stallion sperm storage (Giaretta et al., ) and that it could even become dangerous if supplemented at high concentrations. Other authors obtained similar results in porcine sperm (Martin‐Hidalgo et al., ), concluding that this antioxidant is not suitable for sperm preservation.…”
Section: Discussionmentioning
confidence: 71%
“…Other authors obtained similar results in porcine sperm (Martin-Hidalgo et al, 2013), concluding that this antioxidant is not suitable for sperm preservation.…”
Section: Discussionmentioning
confidence: 73%